Heisenberg.s Turbulent Spectral Theory Determining the Filtering Procedure in les Models - Degrazia, Gervásio A.; Acevedo, Otávio C.; Velho, Haroldo F. de Campos; Puhales, Franciano S. (Ciência e Natura, 2007)
Heisenbergs turbulent spectral theory determining thefiltering procedure in LES models